2021
DOI: 10.1016/j.eclinm.2021.100947
|View full text |Cite
|
Sign up to set email alerts
|

Global changes in maternity care provision during the COVID-19 pandemic: A systematic review and meta-analysis

Abstract: Interpretation: Reduced maternity healthcare-seeking and healthcare provision during the COVID-19 pandemic has been global, and must be considered as potentially contributing to worsening of pregnancy outcomes observed during the pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(117 citation statements)
references
References 80 publications
(205 reference statements)
2
94
0
2
Order By: Relevance
“…Likewise, one of the individual characteristics that has been most influential in terms of new barriers created by the pandemic is fear of contagion [83][84][85][86]88,89,94,95,97], an aspect that has been discussed in many publications, including opinion articles [113,[137][138][139][140][141][142], and also played a highly significant role in previous epidemics as a factor causing problems or delays in seeking medical care [2,21,24,26,72,76,101,108,143,144]. Other factors reported include the stigma associated with seeking care [84,89,93,94,97], also described in other publications [109,145], and users playing down the need for medical treatment [84,94,98] and perceiving a lack of response on the part of the health services [85,88].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, one of the individual characteristics that has been most influential in terms of new barriers created by the pandemic is fear of contagion [83][84][85][86]88,89,94,95,97], an aspect that has been discussed in many publications, including opinion articles [113,[137][138][139][140][141][142], and also played a highly significant role in previous epidemics as a factor causing problems or delays in seeking medical care [2,21,24,26,72,76,101,108,143,144]. Other factors reported include the stigma associated with seeking care [84,89,93,94,97], also described in other publications [109,145], and users playing down the need for medical treatment [84,94,98] and perceiving a lack of response on the part of the health services [85,88].…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 , 6 In addition, many settings experienced changes in healthcare access and availability. 7 A recent meta-analysis identified 16 studies assessing the impact of the COVID-19 pandemic on preterm birth, 12 of which were conducted in high-income countries (HIC). 8 Although these individual studies reported conflicting findings, a subgroup analysis of the HIC studies suggested some evidence of a significant decrease in the incidence of preterm birth following the start of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal and child health care services need to be sustained as these require regular follow-up and a continuous supply of medicines [ 10 ]. A recent systematic review and meta-analysis reported that during the COVID-19 pandemic there was about a 38% decline in antenatal care (ANC) appointments globally [ 11 ]. Another scoping review concluded that prenatal care visits declined during the pandemic [ 12 ].…”
Section: Introductionmentioning
confidence: 99%